Persepsi Mahasiswa Teknik Elektro UPI dalam Transaksi Jual Beli di e-Commerce Indonesia dengan Perspektif Islam - Ilhami, Alfi Noviar; Anandayutya, Bagaskara; Fahira, Zalfa Lubna; Jenuri (Ikatan Da'i Indonesia, 2024)
In the industrial era 4.0 where everyone is competing to adopt technology making them inseparable from our lives. Likewise, the trading or buying and selling sector has emerged where new buying and selling places have emerged that use technology using the internet network as the basis for their operations. This platform was then called e-commerce. The aim of this research is to find out what students' views are on buying and selling transactions in e-commerce based on an Islamic religious perspective. The method used is a descriptive method with a qualitative approach by collecting data from sources through interviews on WhatsApp. The students studied were students studying in the Electrical Engineering study program at the Indonesian Education University. The interview results showed that all interviewees used e-commerce as a platform for buying and selling online. The speakers also agreed that e-commerce platforms in Indonesia are in accordance with Islamic religious law, while those that do not comply with Shari'a are on the seller's side who sometimes still trade dishonestly. The source also said that the paylater payment method should be avoided because it contains elements of usury and can make our transactions haram. Thus, it can be concluded that buying and selling transactions in e-commerce are permissible as long as we follow the pillars and conditions of buying and selling in Islam and avoid transactions that contain elements of usury, gharar and fraud.